EFEKTIVITAS PENERAPAN OPAC (ONLINE PUBLIC ACCESS CATALOGUE) DALAM PELAYANAN PUBLIK DI PERPUSTAKAAN MUHAMMAD YUSUF AHMADI - Sri Ambar Rinah; Diah Siti Utari; Achmad Nuzuli; Raja Abumanshur Matridi (Unitri Press, 2019)
The purpose of this study was to measure the effectiveness of the OPAC implementation in public services in the library of Muhammad Yusuf Ahmadi in Riau Islands province. As a search tool, which serves community, the effectiveness of the information system facility needs to be measured in order to optimize its function. This research method is quantitative descriptive, using primary data through questionnaires.The results showed that the effectiveness of OPAC application (Online Public Access Catalog) in public services can be said effective. This can be seen from the percentage score of each subvariable, for the quality of the system at 61.3%, the quality of information at 53.8%, the quality of service at 46.2%, the use of 46.2%, user satisfaction at 57%, and net benefits at 48.4%, all is effective. It can be concluded that the application of OPAC in public services in the Muhammad Yusuf Ahmadi Library of Riau Islands Province is effective, ranging from 71.4-88.1 (63.4%). The suggestions are that the Department of Library and Archives of the Riau Islands Province disseminate information to the public about the use of OPAC, and to be better in improving the quality of service.